Efekat hidrokineziterapije na ishod rehabilitacije kod pacijenata nakon ugradnje vještačkog zgloba kuka - Dragicevic-Cvjetkovic, Dragana M; Manojlović, Slavko; Gligić, Monika (Scripta Medica, 2020)
Background/Aim: Total hip replacement is considered as one of the most successful treatment methods in orthopaedic surgery of the 20th century, since it significantly improves the quality of life of the individuals with coxarthrosis. Protocols and the organisation of the postoperative rehabilitation differ significantly around the world. The aim of this study was to investigate the effect of hydrokinesitherapy on the rehabilitation outcome in patients after total hip replacement under in-patient conditions.Methods: This prospective clinical trial included a total of 100 patients of both genders, average age 59.11 ± 8.85 years, which were admitted to the in-patient postoperative rehabilitation after total hip replacement. Patients were randomised in two groups: group A (n = 50) that was subjected to rehabilitation program with hydrokinesiherapy and group B (n = 50) that was subjected to rehabilitation program only. The parameters registered were: the range of movement in the operated hip, the circumference of the femoral musculature and the Western Ontario and McMaster Universities Osteoarthritis Indeks (WOMAC index) at admittance and discharge from in-patient rehabilitation.Results: The average values of hip flexion with extended knee, extension and external hip rotation were significantly better in group A (p < 0.05). The values of the circumference of the femoral musculature and WOMAC index in patients from group A were significantly better on discharge compared to the admission. Also, this group had a statistically significantly better values of the circumference of the femoral musculature and value of WOMAC index at discharge compared to patients from group B (p < 0.05).Conclusion: Hydrokinesitherapy as a part of the protocol for postoperative rehabilitation in patients after total hip replacement leads to a faster improvement of the functional status of the operated hip and patient's quality of life.
Keywords: Rehabilitacija; Hidrokineziterapija; Totalna zamjena kuka